2019
DOI: 10.1111/jvp.12762
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in activated T‐cell cytokine expression in healthy dogs over the initial 7 days of twice daily dosing with oral cyclosporine

Abstract: Cyclosporine is a powerful T‐cell inhibitor used in the treatment of immune‐mediated and inflammatory diseases in the dog. There is limited information on how to best monitor patients on cyclosporine therapy. Currently, pharmacokinetic and pharmacodynamic assays are available. Pharmacokinetic assays that measure the concentration of cyclosporine in the blood are used to assess if an appropriate drug concentration has been achieved; however, target blood drug concentrations have not been shown to reliably corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There were no significant differences between the three disease states ( 42 ). Previous studies found significant suppression of IL-2 expression within 24 h of oral dosing in healthy dogs treated with cyclosporine ( 43 ), however, given the significantly higher baseline IL-2 expression found in our MUO patients, it is reasonable to assume a longer period will be required to fully suppress their T-cell function. When pharmacodynamic testing was available, it was the laboratories recommendation to aim for moderate suppression correlating to 50–80% suppression ( 44 ).…”
Section: Introductionmentioning
confidence: 62%
“…There were no significant differences between the three disease states ( 42 ). Previous studies found significant suppression of IL-2 expression within 24 h of oral dosing in healthy dogs treated with cyclosporine ( 43 ), however, given the significantly higher baseline IL-2 expression found in our MUO patients, it is reasonable to assume a longer period will be required to fully suppress their T-cell function. When pharmacodynamic testing was available, it was the laboratories recommendation to aim for moderate suppression correlating to 50–80% suppression ( 44 ).…”
Section: Introductionmentioning
confidence: 62%
“…4 Cyclosporine, administered orally, reaches peak suppressive effects on T-cell function within a week of commencing therapy, and therefore, for this study, pharmacodynamic monitoring was commenced on or after Day 8 of cyclosporine. 15 The time required to achieve maximum anti-inflammatory and immunosuppressive effects with metronidazole, on the other hand, is largely unknown. Therefore, when metronidazole was added to cyclosporine therapy, blood samples for pharmacodynamic monitoring were not obtained for a minimum of 3 weeks following the addition of metronidazole.…”
Section: Discussionmentioning
confidence: 99%
“…For each collected blood sample, an unactivated sample and an activated sample were plated with 12.5 ng/mL of phorbol 12-myristate 13-acetate m (PMA) with 0.8 μM of ionomycin m being added to the activated sample as previously described by the Pharmacodynamic Laboratory. 15 The samples were then incubated for 5 h at 37 °C and 5% CO 2 . After the incubation, the RNA was extracted using the protocol previously published by the Pharmacodynamic Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…With each medication, drugs were administered for 7 days, followed by a minimum recovery period of 21 days between dosing with another medication. In previous studies of cyclosporine, maximal changes in cytokine expression were seen within 1 week of commencing the drug, and cytokine expression had returned to values before treatment within 2 weeks of discontinuing the medications . After each recovery period, the dogs switched groups, and the study was continued until all dogs had received all medications.…”
Section: Methodsmentioning
confidence: 99%
“…Four dogs were intact females and 4 were neutered males, with a median age of 2 years (range, 1.3‐7.3 years). Typically, 6‐8 dogs are used for standard pharmacokinetic and pharmacodynamic studies, as described by Riviere, and published by others . Dogs were deemed healthy by detection of no abnormalities on physical examination and a minimum data base (including a complete blood count, serum biochemistry, urinalysis) as well as heartworm testing.…”
Section: Methodsmentioning
confidence: 99%